Pengarauh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Studi Kasus Badan Pengelolaan Keuangan Pendapatan Dan Asset (BPKPA) Kabupaten Bener Meriah - Ikelmi Rejeki; Jamaluddin; Umar Iskandar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The problem of budget absorption capacity every year is a routine problem for local governments in every budget period. According to the data collected, regional tax revenues and regional levies in Bener Meriah Regency as part of the source of Original Regional Income revenue have decreased. This decrease was caused by the failure to achieve regional tax and regional levy budget targets. The aim of this research is to analyze and prove how much influence regional taxes and regional levies have on the original regional income of Bener Meriah Regency for 2019-2023. The population in this study is all tax collection receipts in the bookkeeping and balancing fund division of Bener Meriah Regency. This research uses quantitative data. Data can be accessed via the official BPKPA website for Bener Meriah Regency. The sample used is the Bener Meriah Regency Realization Report for the 2019-2023 fiscal year. The data analysis used is panel data regression analysis and the tests used are the T test, F test and coefficient of determination. The research results show that regional taxes have an effect on PAD. Meanwhile, regional levies have no effect on PAD. Meanwhile, simultaneously, the stimulus components measured by regional tax and regional levy variables have an effect on PAD.